2023
DOI: 10.1097/gox.0000000000005051
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Exosomes in Aesthetic Plastic Surgery: A Review of Current Literature

Abstract: Background: Despite an increasing surge of exosome use throughout the aesthetic arena, a paucity of published exosome-based literature exists. Exosomes are membrane-bound extracellular vesicles derived from various cell types, exerting effects via intercellular communication and regulation of several signaling pathways. The purpose of this review was to summarize published articles elucidating mechanisms and potential applications, report available products and clinical techniques, and prompt further investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 63 publications
(128 reference statements)
0
5
0
Order By: Relevance
“…1 Exosomes are nanovesicles that transport bioactive molecules to regulate cell behavior and ECM remodeling. [2][3][4][5] However, current exosome products lack ECM, which plays a crucial role in modulating their uptake, distribution, and signaling effects. The ECM is a complex network of structural and signaling molecules that control cell fate and tissue repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Exosomes are nanovesicles that transport bioactive molecules to regulate cell behavior and ECM remodeling. [2][3][4][5] However, current exosome products lack ECM, which plays a crucial role in modulating their uptake, distribution, and signaling effects. The ECM is a complex network of structural and signaling molecules that control cell fate and tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are complex nanovesicles that are continuously released by cells into the extracellular environment. 2 With a diameter of about 40–100 nm (Fig. 1 ), they contain various biomolecules that interact dynamically with the extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that human ADSCs within the dermal white adipose tissue have stimulatory effects on DPCs and promote HF cycling via extracellular vesicles and complex signaling pathways. 15,[42][43][44][45][46][47] Finally, HF organoids 48 and 3D scaffolds (Fig. 4B) are emerging solutions with clinical applications in virtually all aspects of regenerative plastic surgery.…”
Section: Table 3 Advantages and Disadvantages Of Each Technique For H...mentioning
confidence: 99%
“…Exosomes derived from adiposederived stem cells, for example, can carry factors that support tissue regeneration, contributing to better outcomes in aesthetic procedures. [39] Exosomes possess antiinflammatory properties, which can be beneficial in managing inflammatory skin conditions.…”
Section: Regeneration Properties Of the Exosomes In Few Fields Of Med...mentioning
confidence: 99%